Numerical Study on the Mechanical Properties of Transmission Tower K-Joints under Cyclic Loading - Jia-xiang Li; Chao Zhang; Shu-hong Wang; Sheng-qiang Yin (Shock and Vibration)
During the vibration of a transmission tower, the joints will be subjected to a reciprocating load. To obtain the accurate state of the transmission tower under the load, the mechanical properties of the joints under the vibration load must be considered. In this paper, the mechanical properties of typical K-joints in transmission tower structures are studied by numerical simulation. The failure mode of the K-joint under cyclic loading is also analyzed. The mechanical properties of the K-joint are discussed from the aspects of hysteretic characteristics, stiffness degradation, energy dissipation capacity, and ductility evaluation, and the influencing factors are discussed. The results show that the failure mode of the K-joint is related to the bolt grade and steel strength. When analyzing K-joints, the moment-rotation hysteresis curve should be combined with the realistic parameters of joints to consider the hysteretic behavior of the K-joint. The results provide a theoretical reference for the accurate modeling of transmission towers.